1997
DOI: 10.1002/bbpc.19971010404
|View full text |Cite
|
Sign up to set email alerts
|

Description of solvent effect on the visible absorption spectrum of fluorenone radical anion

Abstract: The solvatochromic shift of the most intensive band of fluorenone radical anion (FN*‐) in the visible region has been examined in 10 polar formally aprotic media. It has been found that this shift depends on the solvent acceptor number (AN) and static dielectric constant (D) according to planar regression: It is suggested that the ground state of FN*‐ is relatively stabilized in a solvent with a high acceptor number and the dipole moment of the solute increases during an excitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…This confirms the presence of deactivation modes other than fluorescence and intersystem crossing. While fluorenone is known to readily undergo photoreduction to form a radical anion, , the presence of this intermediate can be precluded in part owing to the absence of a visible radical anion in the transient absorbance measurements. Moreover, the formation of radical ions would eventually lead to product degradation with prolonged irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…This confirms the presence of deactivation modes other than fluorescence and intersystem crossing. While fluorenone is known to readily undergo photoreduction to form a radical anion, , the presence of this intermediate can be precluded in part owing to the absence of a visible radical anion in the transient absorbance measurements. Moreover, the formation of radical ions would eventually lead to product degradation with prolonged irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…DMF was purchased as Fluka certified solvent for UV spectroscopy and used without purification. TEAP from Merck was purified by recrystallization from triply distilled water and vacuum-dried at 50ЊC; its concentration in solutions was 0.1 M. A spectroelectrochemical cell and apparatus, as well as the procedures and conditions of the experiments, were the same as those used previously in this laboratory (14).…”
Section: Methodsmentioning
confidence: 99%
“…The magnitudes of blue shifts for Bp – are larger than those for Fl – in the case of the gas-phase anions solvated with a single polar molecule, whether it is aprotic or protic . This trend holds for the fully solvated anions in solutions or matrices of aprotic solvents. Yet, it was reported that blue shifts of Fl – in protic solvents are much larger than those of Bp – . ,, Figure shows a graph of photoabsorption peak shifts relative to those in the gas phase for Fl – and Bp – , with respect to E T (30) of several solvents, which is one of the most accepted solvent polarity parameters. , …”
Section: Introductionmentioning
confidence: 95%
“…Solvent effects on electronic structures of molecules often result in shifts of optical transition energies, which have been widely investigated to be correlated with the chemical reactivity in condensed phases. Electronic spectra of aromatic ketyl anions (i.e., radical anions of aromatic carbonyl compounds) have fascinated many researchers for a long time, because significant solvatochromic shifts are observed for the intramolecular charge-transfer (ICT) absorption band, where most population of the excess electron moves from the carbonyl (CO) group to the aromatic rings. Larger solvation energy in the electronic ground state relative to the excited state causes a blue shift of the absorption peak.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation